Anaerobic biodegradation of brown grease and its potential as a source of renewable energy - Heindel, Amy; Lee, Ross; Spracklin, Dan; Duran, Metin (Frontiers in Environmental Engineering, 2024)
The purpose of the study was twofold. The first was to study the anaerobic digestibility and the biochemical methane potential (BMP) of brown grease (BG)–fats and oils collected from restaurants and similar food production facilities. The second objective was to investigate the effects of adding dry, food waste derived hydrochar to enhance the digestion process, specifically as a possible in situ agent to improve biogas quality. The BMP tests involved various BG loadings between 3 and 30 g BG/L. The results indicate that BG is highly digestible under anaerobic conditions with 354 mL CH4/g COD equivalent of BG at 1 atm and 35°C testing conditions, which translates into 28 million gasoline gallon equivalent (GGE) potential energy that could be recovered by anaerobically digesting or co-digesting BG. The particular hydrochar investigated in this study did not show any potential to increase biogas CH4 content.